2002
DOI: 10.1002/mrc.1122
|View full text |Cite
|
Sign up to set email alerts
|

Locally anisotropic motion in a macroscopically isotropic system: displacement correlations measured using double pulsed gradient spin‐echo NMR

Abstract: We propose a novel application of double pulsed gradient spin-echo NMR in which two pairs of gradient pulses are used successively to encode the spin magnetization. These pairs were applied with gradient directions collinear and orthogonal, and the results were compared. The method can be used to detect local diffusion anisotropy even when the distribution of domain directors in the sample is isotropic. The degree of the difference between collinear and orthogonal echo attenuation responses indicates the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
117
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 16 publications
0
117
0
Order By: Relevance
“…This approach becomes ambiguous for more complex materials where several mechanisms could give the same signal attenuation. More recently, the microscopic anisotropy is detected in double-PGSE experiments by diffusion encoding in two separate time periods [26], giving characteristic signal modulations for data obtained with collinear and orthogonal displacement encoding [27][28][29] or when systematically varying the angle between the directions of displacement encoding [26,30,31]. A double-PGSE scheme to quantify microscopic anisotropy in terms of compartment eccentricity, independent of the macroscopic anisotropy, has recently been suggested [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach becomes ambiguous for more complex materials where several mechanisms could give the same signal attenuation. More recently, the microscopic anisotropy is detected in double-PGSE experiments by diffusion encoding in two separate time periods [26], giving characteristic signal modulations for data obtained with collinear and orthogonal displacement encoding [27][28][29] or when systematically varying the angle between the directions of displacement encoding [26,30,31]. A double-PGSE scheme to quantify microscopic anisotropy in terms of compartment eccentricity, independent of the macroscopic anisotropy, has recently been suggested [32].…”
Section: Introductionmentioning
confidence: 99%
“…Here we implement a numerically optimized version of the q-MAS pulse sequence [37] on a high-performance microimaging system, limited to specimens with maximum 10 mm diameter, and on a standard whole-body clinical scanner. The efficiency of the q-MAS sequence is demonstrated using two materials with pronounced water diffusion anisotropy: lyotropic liquid crystals [24,25,27,34,[38][39][40] and pureed asparagus [41][42][43][44]. For contrast, a yeast cells suspension is used, exhibiting two isotropic diffusion components [34,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Variants of this pulse sequence have been considered for and found useful in various applications. [3][4][5][6][7][8][9][10] The simplest version of such sequences employs only two pairs of gradients; a spin-echo version of this double-PFG sequence is shown in Fig. 1͑a͒.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have explored NMR scattering of multiple orientations, which measures the correlation of displacement along different orientations by tracking the spatial history of molecules with different combinations of gradient orientations. [19][20][21] For instance, Cheng and Cory showed that the two-dimensional multiple NMR scattering technique ͑double PGSE͒ can detect anisotropy in randomly oriented yeast cells, 19 and they established the theory for such techniques.…”
Section: B Multiple Diffusion Nmr Scattering Experimentsmentioning
confidence: 99%
“…Recently, Callaghan and Komlosh 21 have used double PGSE to detect microscopical anisotropy of a polydomain lyotropic liquid crystal sample which is macroscopically isotropic material due to the random orientation of the domains. A difference between echo attenuations in the low q regime with different combinations of gradient directions can indicate microscopic anisotropy.…”
Section: B Multiple Diffusion Nmr Scattering Experimentsmentioning
confidence: 99%